Changes in children's oral health related quality of life following dental treatment under general anesthesia - Seyed Ebrahim Jabarifar; Ali Reza Eshghi; Mitra Shabanian; Shahrzad Ahmad (Wolters Kluwer Medknow Publications, 2009)
Background: Children's oral health related quality of life (OHRQoL) evaluates the impacts of oral daily activities of children and family on quality of life. Oral health related quality of life as outcome can be used to evaluate the dental health services. This study aimed to assess the extent to which den-tal treatment under general anesthesia affects quality of life of children and their families. Methods: One hundred parents of 3-10 year-old children who needed dental treatment under general anesthesia completed a parent-children perception questionnaire (P-CPQ) and family impact scale (FIS) before, and 4 weeks after dental treatment under general anesthesia. The questionnaire had statements related to oral health, functional limitation, emotional state and well being social well-being and family issues. Data were analyzed using SPSS version 11.5. Results: The mean scores and standard deviations of oral health quality of life of the children before and after dental treatment were 43.3 ± 7.14 and 39.24 ± 5.47 respectively. The mean scores of FIS before and after dental treatment were 8.00 ± 3.21 and 3.66 ± 2.62, respectively. The effect size of mean differences in P-CPQ and FIS scores were 1.84 ± 1.64 and 1.35 ± 4.34, respectively. Conclusion: Provision of dental treatment under general anesthesia for uncooperative, young chil-dren with extensive dental problems had significant effects on quality of life of both children and their families.